Innovative methods in teaching psychiatry to medical students - Lobo, Antonio; Cámara, Concepción de-la; Campos, Ricardo; Ventura, Tirso; Marco, Carlos; Campayo, Antonio; Dourdil, Federico; Barcones, Mari Fé; Saz, Pedro (The European journal of psychiatry, 2015)
Background and Objectives: To test the conjecture that the innovative method to teach psychosomatic psychiatry previously reported will be confirmed as beneficial in the training of medical students in the field of general psychiatry. Methods: The emphasis in this course is placed on the discussion of clinical cases, bed-side clinical teaching, and a research-oriented part. The “Innovative Teaching Plan” (ITP) is intended to train student-leaders to guide small groups (SG) of students. The results of an intensive clerkship on bedside teaching are also studied. Trainee performance was assessed by the marks in the final examination, and a reliable and valid tool, the Medical Teaching Quality Questionnaire (MTQQ) was used to document trainee satisfaction. The results of five academic courses are presented in this report. Results: External experts consulted assured that the content of the course was adequate. Eight hundred and thirty eight medical students have completed the learning course in the study period, and 418 (one of the two groups) completed the evaluation with the MTQQ. Most items related to the students' satisfaction were rated “high” or “very high”, including the items asking about the usefulness of the course for physicians, the quality of the teaching methods and the bedside teaching. In relation to innovation, the discussion of clinical cases in small groups was also very satisfactory and the “enhancement of a researcher's mind” was rated “high” or “very high” by 1/3rd of medical students. The utility of the yearly evaluation of the quality of teaching methods was supported by results showing that items scored not favourably in the initial evaluation were considerably improved in the follow-up evaluations, when modifications in the method were introduced. Conclusions: Good performance and high satisfaction of medical students was documented in a course on general psychiatry. Lessons may be drawn to inform about efficient and effective ways of teaching and learning this subject.